Criminal Law Enforcement Regarding Domestic Violence in Pondok Kelapa Subdistrict Central Bengkulu: A Qualitative Study from the Victims’ Perspective - Muhammad Aldiansyah (Utami Publisher, 2026)
Domestic violence is a criminal offense that directly violates human rights, particularly those of women and children. Although it is specifically regulated by law, the enforcement of criminal law regarding domestic violence at the local level still faces various obstacles. This study aims to analyze the enforcement of criminal law regarding DV in Pondok Kelapa Subdistrict, Central Bengkulu Regency, with a focus on the victims’ perspective. The research method used is qualitative with an empirical-juridical approach. Data were collected through in-depth interviews with DV victims, law enforcement officials, and community leaders, and supported by documentary analysis. The results of the study indicate that the enforcement of criminal law regarding domestic violence has not been optimal due to factors such as patriarchal culture, the victims’ economic dependence, low legal awareness, and a tendency toward informal resolution. This study concludes that there is a need to strengthen victim-centered legal protection and inter-institutional collaboration in addressing domestic violence crimes at the local level.